2019
DOI: 10.1002/gps.5176
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in elevated depressive symptoms in middle‐aged and older adults by rural childhood residence: The important role of education

Abstract: Objectives To quantify inequalities in the prevalence of elevated depressive symptoms by rural childhood residence and the extent to which childhood socioeconomic conditions and educational attainment contribute to this disparity. Methods We identified the prevalence of depressive symptoms among US‐born adults ages 50 years and older in the 1998 to 2014 waves of the Health and Retirement Study (n = 16 022). We compared prevalence of elevated depressive symptoms (>4/8 symptoms) by rural versus nonrural childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…In China, education and income are robustly associated with later life depression [ 5 , 8 ]. Also, factors such as general health during childhood and parental education are highly associated with later depression [ 8 , 10 , 11 ]. Good self-rated health status during childhood [ 8 , 11 ] and a high level of parental education [ 10 , 11 ] are negatively associated with depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, education and income are robustly associated with later life depression [ 5 , 8 ]. Also, factors such as general health during childhood and parental education are highly associated with later depression [ 8 , 10 , 11 ]. Good self-rated health status during childhood [ 8 , 11 ] and a high level of parental education [ 10 , 11 ] are negatively associated with depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, factors such as general health during childhood and parental education are highly associated with later depression [ 8 , 10 , 11 ]. Good self-rated health status during childhood [ 8 , 11 ] and a high level of parental education [ 10 , 11 ] are negatively associated with depressive symptoms. In the Chinese context, hukou (household registration) status, which is categorized into agricultural or non-agricultural, is related to the availability of a wide range of social benefits [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another area for future research is the exploration of whether education mediates the relationship between rural residence in childhood and later life depressive symptom trajectories for women. In one study, individuals who resided in rural areas during childhood had higher depressive symptoms in mid-to-late life, and that effect was mediated by education level (Murchland et al, 2019). Living in rural areas, which tend to have lower-quality education systems, may expose individuals to low-quality education and put residents at higher risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have identified the influence of income and education on depression over the life course (de la Torre-Luque et al, 2019;Friedman et al, 2007;Lorant et al, 2003). Low income and education levels are unequally distributed in rural areas as compared to urban areas (Murchland et al, 2019).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%